Contemporary applications of mudarabah investment account - Abu Shareah, Mahmood Abdel Rahman (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2013)
This research will discuss about one of the most important modes of Islamic equity financing which is Mudarabah by Islamic financial institutions from a shari'ah perspective and which is rarely practiced. To give the Islamic banks a complete shape, there is no other alternative but to implement, practice and popularize the Mudarabah concept specifically for the purpose of mobilizing funds from the surplus sector and to use them for investing activities in the Islamic institutions. This research attempts to suggest possible measures for promoting and eliminating the challenges related to the practice of Mudarabah in order to strengthen the shari' ah basis and realize the socioeconomic objectives of this Shari'ah contract. The research consists of brief information and regulations of Mudarabah, and analysis of selected aspects related to Mudarabah such as legality, current applications of Mudarabah, and to highlight the current applications and structures of Mudarabah in Islamic financial institutions as well as the Shari' ah risk associated with Islamic deposit account and modes of mitigation. The research will also address the modes of risks mitigation in Mudarabah transactions.